THE EFFECT OF E-FILING USE AND TAXPAYER COMPLIANCE LEVELS ON INDIVIDUAL TAX REVENUE BEFORE AND DURING THE COVID-19 PANDEMIC AT THE PRIMARY TAX OFFICE OF CIBEUNYING, BANDUNG - Astuti, Widya Widi; Siregar, Ade Indriani; Banjarnahor, Masria; Novianti, Suci Dwi; Fadilla, Frida; , Silviana (CENTRAL ASIA AND THE CAUCASUS, 2022)
This study aimed to determine the effect of e-filing use on individual tax revenue before and during the Covid-19 pandemic at the Primary Tax Office of Cibeunying, Bandung and taxpayer compliance with individual tax revenue before and during the Covid-19 pandemic at the Primary Tax Office of Cibeunying, Bandung. This research was conducted using descriptive analysis method with secondary data. The sample was obtained using a saturated sampling technique where all the population was sampled. All indicators of this study first passed the classical assumption test, with the final test in the form of a hypothesis test, namely the Mann Whitney test. The hypothesis testing was conducted using SPSS 21 for Windows. The results showed that the use of e-filing had a positive and significant effect on individual tax revenue before and during the Covid-19 pandemic with a significance value of 0.000, and taxpayer compliance had a positive and significant effect on individual tax revenue before and during the Covid-19 pandemic with significance value of 0.023.